Comparison between the Effects of Combination of Atropine plus Glycopyrrolate with Atropine alone on Heart Rate for the Reversal of Muscle Relaxant after General Anesthesia - Muhammad Saadat Ali, Zainab Fareed, Muhammad Azeem Mir, Maria Jamil, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A muscle relaxant is an integral component of general anesthesia. Anticholinesterase drugs employed as their antagonist are associated with certain untoward effects. To counter these undesirable effects, anticholinergic agents, atropine, and glycopyrrolate are often used. Objectives: To compare and quantify the mean change in heart rate in patients receiving atropine (0.5 mg) alone, glycopyrrolate (0.5 mg) alone, and atropine (0.25 mg) plus glycopyrrolate (0.25 mg) after muscle relaxant reversal with neostigmine. Study Design: Randomized controlled trial Place and Duration of Study: Department of Anesthesiology and General Surgery Operation Theatre, Nishtar Medical University Multan from 1st January 2021 to 30th June 2021. Methodology: Ninety patients fulfilling inclusion and exclusion criteria undergoing elective cholecystectomy or ventral hernia repair under general anesthesia were included in this study. Group A (n= 30) received Atropine 0.5mg IV, Group G (n=30) received Glycopyrrolate 0.5mg IV while Group A+G (n=30) received atropine 0.25mg plus glycopyrrolate 0.25mg. Data regarding patients’ age, gender, ASA status, type of procedure and operation time, detailed clinical history, and laboratory investigations were taken for all patients. Heart rate of patients before muscle relaxant reversal and after 3 minutes of reversal was noted and heart rate change was calculated. Results: Mean change in heart rate in group A+G was 9.06±3.55 beats/min, 18.53±9.61 beats/min in group A and 17.26±6.20 beats/min in group G. This difference was statistically significant with a p-value <0.0001. Conclusion: Atropine and glycopyrrolate combination is more effective than atropine or glycopyrrolate alone in preventing the heart rate variability associated with reversal of neuromuscular blockers using neostigmine. Keywords: tropine, Glycopyrrolate, Heart rate.